The Pharmacological Action of Kaempferol in Central Nervous System Diseases: A Review - Silva dos Santos, Jéssica; Gonçalves Cirino, João Pedro; de Oliveira Carvalho, Patrícia; Ortega, Manoela Marques (Frontiers in Pharmacology, 2021)
Kaempferol (KPF) is a flavonoid antioxidant found in fruits and vegetables. Many studies have described the beneficial effects of dietary KPF in reducing the risk of chronic diseases, especially cancer. Nevertheless, little is known about the cellular and molecular mechanisms underlying KPF actions in the central nervous system (CNS). Also, the relationship between KPF structural properties and their glycosylation and the biological benefits of these compounds is unclear. The aim of this study was to review studies published in the PubMed databases during the last 10 years (2010-2020), considering only experimental articles that addressed the isolated cell effect of KPF (C15H10O6) and its derivatives in neurological diseases such as Alzheimer’s disease, Parkinson, Ischemia Stroke, Epilepsy and glioblastoma. 19 publications were included in the present review, which presented recent advances in the effects of KPF on the nervous system. KPF has presented a multi-potential neuroprotective action through the modulation of several pro-inflammatory signaling pathways such as the nuclear factor kappa B (NF-kB), p38 mitogen-activated protein kinases (p38MAPK), and serine/threonine kinase (AKT). In addition, there are different biological benefits and pharmacokinetic behaviors between KPF aglycone and its glycosides. The antioxidant nature of KPF was observed in all neurological diseases through: MMP2, MMP3, and MMP9 metalloproteinase inhibition; reactive oxygen species generation inhibition; endogenous antioxidants modulation as superoxide dismutase and glutathione; formation and aggregation of beta-amyloid (β-A) protein inhibition and brain protective action through the modulation of brain-derived neurotrophic factor (BDNF), important for neural plasticity. In conclusion, we suggest that KPF and some glycosylated derivatives (KPF-3-O-rhamnoside, KPF-3-O-glucoside, KPF-7-O-rutinoside, and KPF-4'-methyl ether) have a multi-potential neuroprotective action in CNS diseases and further studies may make KPF effect mechanisms in those pathologies clearer. Future in vivo studies are needed to clarify the mechanism of KPF action in CNS diseases as well as the impact of glycosylation on KPF bioactivity.